Ring-Opening Polymerization of Bicyclo[2, 2, 1] Heptene Derivatives - Shahada, Lamies (Asian Journal of Chemistry, 2010)
The Diels-Alder reaction of dimethyl fulvene and maleic anhydride gave 7-isopropylidenebicyclo[2, 2, 1]-hept-2-ene-5, 6-dicarboxylic acid anhydride which has been shown to undergo ring-opening polymerization. The catalytic system used being produced by reaction of either tungsten hexachloride or molybdenum pentachloride with tetramethyl tin in chlorobenzene at 70ºC.